Librarians, Undergraduate Research, and Diversity Support Programs: Partnerships Towards Social Justice - Diana Park; Stephanie Ramos (Issues in Science and Technology Librarianship)
Science librarianship has barely scratched the surface when grappling with the injustice in our profession and the disciplines we support. Here we provide one example of how STEM librarians can work within the academy to resist systemic barriers and support students from marginalized communities. This paper will explore how librarians and libraries can partner with various diversity support programs and undergraduate research programs targeted toward undergraduate students with marginalized identities. We will then share the perspective of two women of color who have developed this partnership. This article provides the separate and shared perspectives of a science librarian and undergraduate research director in working together to remove barriers students may face in their higher education journeys by creating relationships and meaningful connections.